Transforming growth factor-bold beta1 gene polymorphisms associated with chronic obstructive pulmonary disease in Chinese population - Su Zhi-guang; Wen Fu-qiang; Feng Yu-lin; Xiao Min; Wu Xiao-ling (Acta Pharmacologica Sinica, 2016)
Aim: To determine the frequencies of polymorphism and haplotype in the transforming growth factor-beta 1 (TGF-beta1) gene promoter in the Chinese population and to investigate the susceptibility of this population to chronic obstructive pulmonary disease (COPD). Methods: The target fragments of the TGF-beta1 gene promoter were amplified and analyzed by polymerase chain reaction-restriction fragment length polymorphism technique in 84 COPD patients and 97 age- and sex-matched healthy controls. The test for Hardy-Weinberg equilibrium was performed using HWE program of the LINKUTIL package and statistical analysis was carried out with the SPSS statistical package. An expectation maximization algorithm was used for the pairwise linkage disequilibrium test and haplotype analysis. Results: More carriers of the -800A allele, or fewer carriers of the -509T allele, were detected in the COPD patients compared with the non-symptomatic control subjects [for the -800A allele, 29.8% vs 14.4%, respectively, chi2=6.257, degrees of freedom (df)=1, P=0.012; for the -509T allele, 27.3% vs 44.3%, respectively, chi2=5.582, df=1, P=0.018]. The prevalence of the -800A allele was significantly higher in the COPD patients than in control subjects (P=0.009), whereas the frequency of the -509T allele was significantly higher in control subjects than in the COPD patients (P=0.008). In addition, this distribution tendency for the -800A or -509T allele was similar in heavy smokers (smoking history greater than or equal to20 pack years); (number of packs of cigarettes per day multiplied by the number of years of smoking) chi2=7.235, P=0.007, and chi2=5.636, P=0.018, respectively). The linkage disequilibrium was found between -800 Gright arrowA and -509 Cright arrowT (D